2013
DOI: 10.1080/13854046.2013.796406
|View full text |Cite
|
Sign up to set email alerts
|

Normative Performance on the Brief Smell Identification Test (BSIT) in a Multi-Ethnic Bilingual Cohort: A Project FRONTIER Study1

Abstract: The Brief Smell Identification Test (BSIT) is a commonly used measure of olfactory functioning in elderly populations. Few studies have provided normative data for this measure, and minimal data are available regarding the impact of sociodemographic factors on test scores. This study presents normative data for the BSIT in a sample of English- and Spanish-speaking Hispanic and non-Hispanic Whites. A Rasch analysis was also conducted to identify the items that best discriminated between varying levels of olfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 44 publications
1
58
2
Order By: Relevance
“…These differences could have resulted from procedure effects, although the NHANES pilot testing and modifications of the PST to ensure cultural appropriateness aimed to minimize procedural differences. The parent forms of the PST, the 12-item B-SIT and 40-item UPSIT, have been shown to perform well in testing olfaction across diverse groups including Hispanics [74, 78] and Asians [79]. Other population-based studies also have reported differences in olfactory testing across race/ethnic groups [63, 80].…”
Section: Discussionmentioning
confidence: 99%
“…These differences could have resulted from procedure effects, although the NHANES pilot testing and modifications of the PST to ensure cultural appropriateness aimed to minimize procedural differences. The parent forms of the PST, the 12-item B-SIT and 40-item UPSIT, have been shown to perform well in testing olfaction across diverse groups including Hispanics [74, 78] and Asians [79]. Other population-based studies also have reported differences in olfactory testing across race/ethnic groups [63, 80].…”
Section: Discussionmentioning
confidence: 99%
“…7 Furthermore, the B-SIT is not as effective at discriminating various levels of smell identification. 25 This potential lack of discrimination may lead to an under reporting of olfactory dysfunction which may bias effect estimates of change towards null hypotheses and limit our ability to detect true differences between treatment modalities. The high level of normosmics led to the evaluation of the cohort in sub-groups of normal olfaction and impaired olfaction.…”
Section: Discussionmentioning
confidence: 99%
“…The 12‐item B‐SIT is a subset of the 40‐item UPSIT and may have similar accuracy for the prediction of dementia . For this report, B‐SIT scores were computed from the twelve B‐SIT items within the UPSIT.…”
Section: Methodsmentioning
confidence: 99%
“…Distributions and group differences in demographic and clinical variables were examined by χ 2 , t‐test, and general linear models as appropriate. B‐SIT score of 11 or 12 of 12 indicates no odor identification deficit in a broad range of individuals and BOMC score ≤5 of 28 is in the normative range for middle‐aged to older adults . Therefore, these cutoff points, which represent stringent criteria, were used in the main analyses.…”
Section: Methodsmentioning
confidence: 99%